BIOCHEMICAL INVESTIGATION ON EDIBLE MOLLUSCS OF KERALA I. A STUDY ON THE NUTRITTIONAL VALUES OF SOME BIVALVES - SURYANARAYANAN, H; ALEXANDER, K M (Fishery Technology, 2025)
Data on the biochemical constituents and food vaiues of five commercially important edible bivalves of Kerala, LameTlidens corrianus; Corbicuta strfatella, Mytilus edulis.,. Vellorita cohinensis and OstreCI’ cucullata have been presented. Physiological significance of the variations have been discussed. Present study reveals that the bivalve: meat compares favourably with the common food fishes with regard to their caloric value and hence would be an excellent and economic: source of nutrition for our people